The German dual vocational education and training system as 'good practice'?. (August 2015) - Deissinger, Thomas
The German Dual System has attracted some considerable attention in recent years, with a number of countries, above all in Southern Europe, trying to introduce similar concepts of structured apprenticeships leading to initial vocational qualifications. Quite manifestly, there is expectation among politicians in particular that such a system might help cope with integration problems of school leavers into the vocational education and training sector and support combating youth unemployment. Focusing on the two 'learning venues', however, seems short-sighted as the German vocational education and training system has more working principles than just the dual learning setting. In contrast to the British approach, the German system trusts in a clear orientation of workplace learning along the lines of an 'occupation' (Beruf). Besides, the German vocational education and training system as a whole is more complex than it seems, with a still weighty 'transition system' and full-time courses in vocational education and training alongside apprenticeships. My argument is that the aspect of 'good practice' has to be relativised both against the background of these structural issues and in the face of recent academic drift in the German education system.